Effect of Fluticasone 250 μg/salmeterol 50 μg and Montelukast on Exhaled Nitric Oxide in Asthmatic Patients - Arthur F Gelb; Colleen Flynn Taylor; Chris M Shinar; Carlos A Gutierrez; Noe Zamel (Canadian Respiratory Journal)
BACKGROUND: Monitoring noninvasive biomarkers of inflammation is an important adjunct in asthma therapy.